2017
DOI: 10.1159/000457806
|View full text |Cite
|
Sign up to set email alerts
|

Postradiation Matrix Metalloproteinase-20 Expression and Its Impact on Dental Micromorphology and Radiation-Related Caries

Abstract: Recent evidence suggests that head-and-neck radiotherapy (HNRT) increases active forms of matrix metalloproteinase-20 (MMP-20) in human tooth crowns, degrading the dentin-enamel junction (DEJ) and leading to enamel delamination, which is a pivotal step in the formation of radiation-related caries (RRC). Additional participation of enzymatic degradation of organic matrix components in caries progression was attributed to MMP-20 in dentin. Therefore, the current study tested the hypothesis that MMP-20 is overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
(45 reference statements)
2
12
0
1
Order By: Relevance
“…This result corroborates those of previous works suggesting that both the direct effects of HNRT and the clustering of oral symptoms caused by the treatment, especially the reduction of the salivary flow, have an important role in the onset and progression of RRC. 7,[19][20][21] In our study, the median time for RRC onset was 11.5 months, which is consistent with that reported in the literature, which describes the appearance of RRC after a period of approximately 12 months following the conclusion of HNRT. 3,22 Most of our cases were diagnosed as advanced RRC lesions; the reason may be patients' failure to comply with dental follow-up after the onco-logic treatment was completed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result corroborates those of previous works suggesting that both the direct effects of HNRT and the clustering of oral symptoms caused by the treatment, especially the reduction of the salivary flow, have an important role in the onset and progression of RRC. 7,[19][20][21] In our study, the median time for RRC onset was 11.5 months, which is consistent with that reported in the literature, which describes the appearance of RRC after a period of approximately 12 months following the conclusion of HNRT. 3,22 Most of our cases were diagnosed as advanced RRC lesions; the reason may be patients' failure to comply with dental follow-up after the onco-logic treatment was completed.…”
Section: Discussionsupporting
confidence: 91%
“…This axial/transversal progression seen in our sample indicates that the "strangulation" process that leads to crown amputation is the most advanced stage of RRC in terms of structure loss. 5,11,20,28,29 Remarkably, the results of our study revealed high scores for both the ICDAS and the PRDI, reinforcing the fact that RRC lesions are mainly diagnosed in late stages and, therefore, are identified when there is already severe tooth destruction. The ICDAS severity in our sample is not compatible with that reported in previous works that assessed conventional caries for an epidemiologic purpose and presented a higher prevalence of initial scores.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results indicate a possible molecular mechanism underlying the rapid onset and progression of radiationinduced caries. Contrarily, in recent studies, these direct effects of radiation were not observed, with no evident differences in the expression and activity of MMP-2 and MMP-9 in the DEJ and dentin-pulp complex of irradiated teeth [Gomes-Silva et al, 2017b], and MMP-20 overexpression not factored into analysis in these groups of teeth [Gomes-Silva et al, 2017a]. While these studies used teeth extracted from patients who had undergone radiotherapy, our study used teeth submitted to the radiation protocol after extraction.…”
Section: Discussionmentioning
confidence: 74%
“…Clinical research suggests that the mechanical properties of the enamel are negatively affected by HNRT; however, no consensus has been established in the literature concerning the ability of ionising radiation to be directly injurious to the DEJ, increasing the risk for enamel delamination and RRC progression (15)(16)(17). Despite controversial results regarding radiation-related damage to the DEJ microstructure in HNC patients (4,10,18), many studies aimed to evaluate that enzymatic expression favours RRC progression (9,15,19,20). Therefore, this systematic review aimed to evaluate if HNRT should be considered an independent risk factor to damage the physicochemical properties of the DEJ in cancer patients.…”
Section: Introductionmentioning
confidence: 99%